FACTORS ASSOCIATED WITH THE LEVEL OF YOUTH ATTENDANCE AT THE YOUTH POSYANDU IN THE CIPONDOH HEALTH CENTER IN 2022 - Suherman; Zuyyina Adhal Tasyiawurin (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
Based on the Indonesian Health Profile (2021), Banten Province is one of the provinces whose health service coverage for school-age children is still limited. Apart from that, the attendance rate of teenagers at the youth Posyandu in the Cipondoh Community Health Center working area was still below the target in the last year, namely only 15% of the target set at 70%. This research design used a cross-sectional design with a sample of 50 teenagers. The sampling technique uses total sampling. Data analysis using the Chi-Square test (α 0.005). There is a significant relationship between knowledge (p=0.000), distance (p=0.020), peer support (p=0.008), and the level of attendance of teenagers at the youth Posyandu. There is no significant relationship between family support and adolescent attendance at the youth Posyandu. Factors related to the level of attendance of teenagers at the youth Posyandu in the Cipondoh Community Health Center working area in 2022 are knowledge, distance, and peer support. Suggestions that can be given are to empower youth Posyandu cadres in each RW to be able to coordinate teenagers to come to youth Posyandu and carry out activities that can attract teenagers to come to Posyandu.